Retracted: Impact of Green Financing on Carbon Drifts to Mitigate Climate Change: Mediating Role of Energy Efficiency - Chang, Lei; Wang, Jianhe; Xiang, Ziman; Liu, Hongda (Frontiers in Energy Research, 2021)
Climate change mitigation (CCM) has not been mainly understood and assessed in the terms of carbon drifts persisting at provincial level of China, and to respond the question that how green financing is better financing option for CCM. Thus, our study intends to test the role of green finance on carbon drifts to manage for the mitigation of climate change. For this, unit root test and panel co-integration technique is applied. Study findings reported that the intricate connection between place-and-time-specific GHG emission reduction responsibilities is significant with 18% and the ‘production’, trading and consumption of carbon allowances with 21% and offsets across vast time-space stretches related carbon drift is significant with 19.5% for climate change mitigation. For such significance, green financing is found imperative indicators which is significant at 27.1% with carbon drifts, and mitigates the climate change with 31.3%, which is, relatively high than usual climate change control practices. Our study also provides detailed policy implication on this topicality for associated stakeholder.